High immunogenicity of virus-like particles (VLPs) decorated with Aeromonas salmonicida VapA antigen in rainbow trout - Yang, Jeong In; Sepúlveda, Dagoberto; Vardia, Irina; Skov, Jakob; Goksøyr, Louise; Sander, Adam F.; Lorenzen, Niels (Frontiers in Immunology, 2023)
The Gram-negative bacterium A. salmonicida is the causal agent of furunculosis and used to be one of the most loss-causing bacterial infections in the salmonid aquaculture industry with a mortality rate of about 90% until the 1990s, when an inactivated vaccine with mineral oil as adjuvant was successfully implemented to control the disease. However, the use of this vaccine is associated with inflammatory side effects in the peritoneal cavity as well as autoimmune reactions in Atlantic salmon, and incomplete protection has been reported in rainbow trout. We here aimed at developing and testing a recombinant alternative vaccine based on virus-like particles (VLPs) decorated with VapA, the key structural surface protein in the outer A-layer of A. salmonicida. The VLP carrier was based on either the capsid protein of a fish nodavirus, namely red grouper nervous necrotic virus (RGNNV) or the coat protein of Acinetobacter phage AP205. The VapA and capsid/coat proteins were expressed individually in E. coli and VapA was fused to auto-assembled VLPs using the SpyTag/SpyCatcher technology. Rainbow trout were vaccinated/immunized with the VapA-VLP vaccines by intraperitoneal injection and were challenged with A. salmonicida 7 weeks later. The vaccine provided protection comparable to that of a bacterin-based vaccine and antibody response analysis demonstrated that vaccinated fish mounted a strong VapA-specific antibody response. To our knowledge, this is the first demonstration of the potential use of antigen-decorated VLPs for vaccination against a bacterial disease in salmonids.